Evaluasi Manajemen Agribisnis Berkelanjutan dan Tata Kelola Usaha Peternakan Sapi Perah di Desa Wiyurejo: Evaluation of Sustainable Agribusiness Management and Dairy Farm Governance in Wiyurejo Village - Wahyudi, Adip; Maulana, Feri Fahrian; Hidayatulloh, Ahmat Fanani; Al Kindy, Muhammad Asyrofi (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2026)
Background: Dairy farm management in Indonesia faces major challenges, including fluctuations in feed prices, limited human resources, and the environmental impact of livestock waste. Wiyurejo Village, as a milk-producing area, faces challenges in implementing sustainable agribusiness management to ensure business continuity and farmer welfare. This study aims to evaluate sustainable agribusiness management in dairy farming in Wiyurejo Village and identify managerial achievements in the management of livestock businesses implemented at the SAE Pujon Milk Cooperative in Wiyurejo Village. Purpose: Providing recommendations to improve the sustainability of dairy farming in Wiyurejo Village. Methods: This study uses a qualitative approach with descriptive data analysis. Data collection was conducted through structured interviews, observations, and questionnaires involving farmers and cooperative managers. Data analysis techniques used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. Results: This study found that sustainable agribusiness management has been well implemented in terms of facilities and infrastructure, selection of superior seeds, and feed management that has been well prepared in advance. The dairy cow maintenance system that has been implemented has also proven to be effective, with farmers adopting an intensive system that allows for better control of livestock. However, livestock waste management, which is still not optimal, such as direct disposal into rivers, is a major obstacle that threatens environmental sustainability. Conclusion: Finally, this study provides important insights into the challenges and opportunities in sustainable dairy farming management. Going forward, improvements in livestock waste management and greater integration between the livestock sector, government, and community are needed to achieve greater sustainability.